Identifikasi Kandungan Mikroplastik pada Perairan Sungai - Adila, Najwa; Windusari, Yuanita (JURNAL KESEHATAN PRIMER, 2024)
The purpose of this study is to identify the content and form of microplastics in the waters of the Musi River, Musi Banyuasin, South Sumatra. This study is descriptive analytical with the determination of the location point of water sampling carried out by purposive sampling of 200 ml with 3 repetitions. The identification results are displayed in the form of an image. In 100 ml of water samples, microplastics were found in the form of fibers (5 particles), films (4 particles), fragments (2 particles), and pellets (1 particle). The most commonly found form of microplastics is fibers with 5 particles. The identification of microplastic content in water in the waters of the Musi River,Musi Banyuasin showed variations in microplastics in the form of fibers, films, fragments and pellets. The colors of microplastics found are brown, red, and green with the most dominant color being brown with a total of 10 particles. The average size of the 12 microplastic particles that have been found is 896.13 μm. The existence of microplastics can harm ecosystems and cause various negative impacts on human health.